2000
DOI: 10.1016/s0006-3223(99)00316-9
|View full text |Cite
|
Sign up to set email alerts
|

Open-label adjunctive topiramate in the treatment of bipolar disorders

Abstract: These preliminary open observations of adjunctive topiramate treatment suggest that it may have antimanic or anticycling effects in some patients with bipolar disorder, and may be associated with appetite suppression and weight loss that is often viewed as beneficial by the patient and clinician. Controlled studies of topiramate's acute and long-term efficacy and side effects in bipolar disorder appear warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
98
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(105 citation statements)
references
References 24 publications
4
98
1
2
Order By: Relevance
“…[63][64][65][66] Rigorously performed, controlled trials, however, failed to find any benefit from use of this drug in bipolar disorder. 67 Topiramate has been commonly prescribed for patients with bipolar disorder, not only because of the expectation that it will prove to be efficacious, but also because of its weight-reducing effects, which are felt to be particularly desirable to counteract the weight gain induced by some other mood stabilizing agents (e.g., valproic acid).…”
Section: Topiramatementioning
confidence: 99%
“…[63][64][65][66] Rigorously performed, controlled trials, however, failed to find any benefit from use of this drug in bipolar disorder. 67 Topiramate has been commonly prescribed for patients with bipolar disorder, not only because of the expectation that it will prove to be efficacious, but also because of its weight-reducing effects, which are felt to be particularly desirable to counteract the weight gain induced by some other mood stabilizing agents (e.g., valproic acid).…”
Section: Topiramatementioning
confidence: 99%
“…In one study, CRH was observed to block NPYinduced feeding in rats, suggesting that CRH overrides the effect of NPY in this behavioral aspect (Heinrichs et al, 1993). Consequently, it is possible that the observed increase in CRH-LI may be of significance to the long-term appetite-suppressive effects of topiramate reported to humans (McElroy et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…In addition to anticonvulsant efficacy, other major clinical observations have been made. Specifically, topiramate has antimanic and anticycling effects in bipolar patients (Calabrese et al, 2001;McElroy et al, 2000). In addition, topiramate treatment has been associated with appetite suppression and weight loss in patients, in particular in overweight individuals (McElroy et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been proposed as a mood stabilizer for patients with bipolar disorders who have not responded to the traditional treatments [7][8][9] . Neuropsychiatric symptoms may emerge after the use of TPM, the most common complaints are: somnolence, dizziness, tiredness, ataxia, headache, depression, and cognitive impairment such as mental confusion, slow reasoning, speech difficulty, and disturbance of memory [10][11][12][13][14][15][16][17][18] .…”
mentioning
confidence: 99%